Pengaruh Return On Equity, Total Asset Turnover dan Net Profit Margin terhadap Nilai Perusahaan pada Perusahaan LQ45 yang Terdaftar di BEI Periode 2023-2025 - Windi Massari; Dian Ayu Andriani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the effect of Return on Equity (ROE), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on firm value in companies included in the LQ45 index listed on the Indonesia Stock Exchange during the 2023-2025 period. The research was conducted because fluctuations in firm value among LQ45 companies indicate that financial performance indicators do not always produce consistent market responses. This study applied a quantitative approach using secondary data obtained from annual financial reports. The sample consisted of 11 companies selected through purposive sampling, resulting in 33 observations. Data were analyzed using multiple linear regression with the assistance of SPSS version 26, preceded by classical assumption testing. The findings reveal that ROE has a positive and significant effect on firm value, while TATO does not significantly affect firm value. In contrast, NPM shows a negative and significant effect on firm value. Simultaneously, ROE, TATO, and NPM significantly influence firm value. The coefficient of determination indicates that the independent variables explain 55.4% of the variation in firm value, whereas the remaining percentage is influenced by other factors outside the research model.